PENCEGAHAN STUNTING MELALUI EDUKASI GIZI REMAJA - Fitriana Noor Khayati; Chori Elsera; Arlina Dhian Sulistyowati; Bintang Syahla Putri Purnomo; Melsa Permata Beta Putri (WASATHON Jurnal Pengabdian Masyarakat, 2026)
Stunting remains a significant national and global health issue. The occurrence of stunting can negatively impact children’s growth, brain development, and cognitive function. In efforts to prevent and reduce stunting rates, the health quality of young people, particularly adolescent girls, is considered crucial in supporting these initiatives. Adolescents play an important role in preventing and reducing the incidence of stunting. The involvement of adolescent in stunting prevention can make a substantial contribution to improving the quality of life for children in the future. Jiwan Village is located approximately 13 km from the center of Klaten, and a portion of adolescents marry at a young age. Many adolescents still lack knowledge about how to prevent stunting. This activity aims to provide nutrition education to adolescent in Jiwan Village. The educational program conducted using brainstorming and lecture-based question-and-answer methods. The media employed will include flipcharts and audiovisual tools. The program implemented in Jiwan Village. The activity was held in Jiwan Village and was attended by 29 teenagers. The results show an increase in average knowledge after education, from 74.5 to 91.7. This activity can improve adolescents' knowledge about stunting prevention.